Comparison of patients undergoing protected high risk percutaneous coronary intervention using either intravascular lithotripsy or rotational atherectomy - Krause, Tobias T.; Afzal, Shazia S.; Gjata, Anida; Lindner, Michael; Saad, Louai; Steinbach, Mirjam; Zayat, Rashad; Haneya, Assad; Werner, Nikos; Leick, Juergen (Frontiers in Cardiovascular Medicine, 2024)
BackgroundTreating heavily calcified vessels is a challenging task in patients with an impaired left ventricular ejection fraction. Percutaneous mechanical circulatory support (pMCS) is increasingly used in patients in high-risk percutaneous coronary intervention (HRPCI).MethodsIn this retrospective registry, we investigated 25 patients undergoing a protected HRPCI receiving either intravascular lithotripsy (IVL + pMCS; n = 11) or rotational atherectomy (RA + pMCS; n = 14). The primary endpoint was defined as peri-interventional hemodynamic stability. The secondary endpoint was defined as major adverse cardiac events (MACE).ResultsPatients in the IVL + pMCS group had a significantly higher mean arterial pressure (MAP) at the end of the procedure (p = 0.04). However, the Δ-change in MAP was not significant [−12 mmHg (±20.3) vs. −16.1 mmHg (±23.9), p = 0.709]. The proportion of patients requiring post-interventional catecholamines was significantly lower in the IVL + pMCS group (p = 0.02). The Δ-change in Syntax Score was not significant between groups (IVL + pMCS −22 (±5.8) vs. RA + pMCS −21.2 (±7.6), p = 0.783). MACE did occur less in the group of IVL + pMCS (0% vs. 20%, p = 0.046). Patients with pMCS insertion as a bailout strategy had a higher probability for in-hospital death (p < 0.001) and the occurrence of the slow-reflow phenomenon was associated with long-term mortality (p = 0.021) in the cox regression analysis.ConclusionsIn our cohort patients in the IVL + pMCS group were hemodynamically more stable which led to a lower rate of catecholamine usage. pMCS as a bailout strategy was associated with in-hospital death and the occurrence of the slow reflow phenomenon with all-cause mortality during follow-up.